Specific heat capacity of the intermetallics ε-Cu3Sn, η/η′-Cu6Sn5, Al3Ni and Al3Ni2. (September 2021) - Saenko, Ivan; Engelhardt, Hannes; Hornig, Philipp; Fabrichnaya, Olga; Lippmann, Stephanie
Abstract: The ε-Cu3 Sn, η/η′-Cu6 Sn5, Al3 Ni and Al3 Ni2 intermetallics have been produced as pure phases by the mushy zone resolidification in a temperature gradient. Powder XRD and SEM/EDX analysis were used for sample characterization. Heat capacity measurements have been performed in temperature ranges starting from 210 K up to temperatures close to the stability limits of the investigated phases. Based on the experimental results, the specific heat capacities of the intermetallics have been described from 0 K using an extended Einstein model. The model was chosen as one of most promising models for describing heat capacities for the 3 rd generation of CALPHAD type thermodynamic databases and as it allows the determination of the standard entropies of intermetallic compounds. Highlights: Synthesis of pure intermetallics w/wo solubility range employing temperature gradients. Cp measurement of ε-Cu3 Sn, η/η′-Cu6 Sn5, Al3 Ni and for the first time Al3 Ni2 . Cp description from 0 K to the maximum stability temperature. Determination of the standard entropy at 298 K of intermetallic compounds.